Conductive Metal–Organic Frameworks for Supercapacitors. Issue 52 (14th July 2022) - Niu, Liang; Wu, Taizheng; Chen, Ming; Yang, Long; Yang, Jingjing; Wang, Zhenxiang; Kornyshev, Alexei A.; Jiang, Huili; Bi, Sheng; Feng, Guang
Abstract: As a class of porous materials with crystal lattices, metal–organic frameworks (MOFs), featuring outstanding specific surface area, tunable functionality, and versatile structures, have attracted huge attention in the past two decades. Since the first conductive MOF is successfully synthesized in 2009, considerable progress has been achieved for the development of conductive MOFs, allowing their use in diverse applications for electrochemical energy storage. Among those applications, supercapacitors have received great interest because of their high power density, fast charging ability, and excellent cycling stability. Here, the efforts hitherto devoted to the synthesis and design of conductive MOFs and their auspicious capacitive performance are summarized. Using conductive MOFs as a unique platform medium, the electronic and molecular aspects of the energy storage mechanism in supercapacitors with MOF electrodes are discussed, highlighting the advantages and limitations to inspire new ideas for the development of conductive MOFs for supercapacitors. Abstract : Conductive metal–organic frameworks (c‐MOFs), as an emerging class of electrode materials, have attracted great attention recently. The efforts hitherto devoted to the synthesis and design of c‐MOFs and their auspicious capacitive performance are reviewed. The recent achievements of developing supercapacitors with c‐MOF electrodes are discussed, from the experimental performance to a fundamental understanding of the energy storage mechanism, highlighting their bottlenecks and perspectives.